COVID-19—The Historical Lessons of the Pandemic Reinforce Systemic Flaws and Exacerbate Inequity - Freeman, Lori Tremmel (American journal of public health (1971), 2021)
The COVID-19 pandemic demonstrates the complex layers of public health practice associated with widespread infectious disease strategies, including containment, mitigation, and medical countermeasures. Through each of these stages of disease intervention, the pandemic exposed deep chasms in our country's ability to ensure that the opportunity to be healthy is an inalienable right for everyone at the highest level of our existence-as a human being-and without regard for one's race, ethnicity, sexual orientation, or economic or social status. I address some of the many examples of how the pandemic further deepened health inequities in our country, how current public health systems failed to address systemic and structural racism rooted in social determinants of health, and how the Public Health 3.0 framework was inadequate in addressing these issues.Inequities in COVID-19 testing emerged early in the pandemic: during containment efforts. Studies confirmed that Black and Hispanic populations had disproportionately higher rates of hospitalization and death from COVID-19 than did Whites.1 In New York City, New York, for example, efforts were undertaken to study testing across the jurisdiction by race/ethnicity and neighborhood, showing that more tests were done in geographic areas with concentrations of White people although non-White areas had more positive tests.